QUANTITATIVE ANALYSIS OF BALTI TRANSLATED IDIOMS INTO ENGLISH BY BS LEVEL STUDENTS AT UNIVERSITY OF BALTISTAN, SKARDU - Zeenat Maryom; Abdul Rehman Mir; Altaf Hussain* (`, 2025)
The current research, in the field of applied linguistics, aims at investigating a range of difficulties related to the accuracy of translation faced by Balti ESL (English as a Second Language) learners at university level. The major focus is on the translation of idioms from Balti language to English language. Furthermore, the study encompasses various strategies to overcoming difficulties and recommending solutions to certain translational issues. With the expended global interaction, research work especially in the realm of translation has grown exponentially worldwide that deals with the issues within languages both inter and intra lingual domains. The study has used a questionnaire with the scheme of idioms from Balti to be translated into English. The mode of analysis is used as close-reading and comparing the translations to the original text. After the collection of the data, the researcher has presented the data on tabular charts using APA format to show data. The students of University of Baltistan have been selected randomly for translating the texts. The study shows that students face difficulty in conceptualizing and translating idioms. One of the reasons for the translational gaps was the translation of idioms sensing word-for-word preferences during the translation process. The researcher discussed the findings at different levels that how the participants as university students, translated the idioms and which type of strategies they used and what sort of barriers they encountered during the translation process. Lastly, this research study will help the future researchers in exploring inter-lingual translational studies especially related to Balti language. Key words: Translations Studies, cultural translation, semantic variations, ESL and ILT